Acute Infection and Maternal Weight Gain: A Correlative Study in Pregnant Women in Bandung City - Fajria Saliha Puspita Prameswari; Widya Astuti; Ahdiyatul Fauza Fauza (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : A woman's body undergoes physiological and immunological adaptations during pregnancy. These adaptations are intended to prepare the mother's body to support fetal growth and development. Nevertheless, the changes that occur can make the mother vulnerable to infections, which may subsequently lead to various pregnancy complications. The pathogens causing these infections can also be transmitted to the fetus, resulting in adverse effects on pregnancy outcomes. Objective : This study aims to analyze the relationship between various types of infection and weight gain during pregnancy. Research Methods/ Implementation Methods : A quantitative study with a cross-sectional design was conducted on 118 pregnant women in the Cidadap Sub-district, Bandung City. Subjects included pregnant women aged 20–35 years, with a single pregnancy, and who routinely attended antenatal care. Pregnant women who were excluded from the study were those diagnosed with chronic diseases (degenerative diseases, cancer, etc.) and those who regularly consumed medication. Data collection involved interviews and direct measurements. The data collected included a history of infection in the last month, weight, height, and pregnancy characteristics. Correlative analysis was performed using the Chi-Square test. Results : Several types of infections were identified, including upper respiratory tract infection, lower respiratory tract infection, urinary tract infection, genital tract infection, and gastrointestinal infection. The analysis results showed that pregnant women who experienced a gastrointestinal infection had a 4.174 times higher risk of having inappropriate weight gain for their gestational age (p=0.041), whereas other types of infection did not show a significant result (p>0.05). The symptoms of gastrointestinal infection experienced included nausea, vomiting (other than morning sickness), diarrhea, and stomach pain. Conclusion/Lesson Learned : Gastrointestinal infection during pregnancy increases the risk of weight gain inappropriate for gestational age in pregnant women. Insufficient weight gain during pregnancy can increase complications during pregnancy and childbirth, and negatively impact the health of both the mother and the fetus. Infection prevention measures before and during pregnancy are essential to maintain the health of the mother and the fetus.